Implementation of the Fath Hijaiyah Game to Improve Quran Reading Skills among Students at SMPN 2 Segeri - Nur Aliyah; Abdul Halik; Buhaerah (Universitas Muhammadiyah Palu, 2026)
his study examines the implementation of the Fath Game Hijaiyah card media in an effort to improve the Quranic reading skills of eighth-grade students at SMPN 2 Segeri, Pangkep Regency. The main issues raised were their low Quranic reading skills, particularly in recognizing similar hijaiyah letters, pronouncing letters according to makhraj and basic tajweed, and low motivation due to monotonous learning methods. This study aims to describe students' initial Quranic reading skills, explain the process of implementing the Fath Game Hijaiyah in learning, and identify obstacles and solutions in its implementation. The study used a Classroom Action Research design with three cycles, each encompassing planning, implementation, observation, and reflection. The subjects were 20 eighth-grade students at SMPN 2 Segeri, selected as a whole class. Data were collected through observations of teacher and student activities, documentation, and a Quranic reading achievement test that assessed aspects of fluency, fluency, and the application of several basic tajweed rules. Data analysis was conducted qualitatively to describe the learning process and changes in learning behavior, and quantitatively to analyze test scores for each cycle. The results showed that in the pre-cycle, only 25% of students achieved mastery, while 75% remained in the incomplete category. After implementing the Fath Game Hijaiyah in cycle I, learning mastery increased to 40%, then further increased to 70% in cycle II, and reached 100% in cycle III. This improvement was reflected in students' ability to distinguish the hijaiyah letters, read more fluently, and reduce basic tajweed errors. From a process perspective, the use of the Fath Game Hijaiyah successfully created a more enjoyable, interactive, and collaborative learning environment, significantly increasing students' motivation and confidence in reading the Quran. Challenges that arose included limited media, differences in students' initial abilities, and learning time allocation. These challenges were addressed through the addition of card sets, study grouping, and more effective time and classroom management. Thus, the Fath Game Hijaiyah has proven effective as an innovative medium for improving the Quranic reading skills of junior high school students.